Patient and healthcare provider views on a patient-reported outcomes portal. (18th September 2018) - Cronin, Robert M; Conway, Douglas; Condon, David; Jerome, Rebecca N; Byrne, Daniel W; Harris, Paul A
Abstract: Background: Over the past decade, public interest in managing health-related information for personal understanding and self-improvement has rapidly expanded. This study explored aspects of how patient-provided health information could be obtained through an electronic portal and presented to inform and engage patients while also providing information for healthcare providers. Methods: We invited participants using ResearchMatch from 2 cohorts: (1) self-reported healthy volunteers (no medical conditions) and (2) individuals with a self-reported diagnosis of anxiety and/or depression. Participants used a secure web application (dashboard) to complete the PROMIS ® domain survey(s) and then complete a feedback survey. A community engagement studio with 5 healthcare providers assessed perspectives on the feasibility and features of a portal to collect and display patient provided health information. We used bivariate analyses and regression analyses to determine differences between cohorts. Results: A total of 480 participants completed the study (239 healthy, 241 anxiety and/or depression). While participants from the tw2o cohorts had significantly different PROMIS scores ( p  < .05), both cohorts welcomed the concept of a patient-centric dashboard, saw value in sharing results with their healthcare provider, and wanted to view results over time. However, factors needing consideration before widespread use included personalization for the patient and their health issues, integration with existing information (eg electronic health records), and integration into clinician workflow. Conclusions: Our findings demonstrated a strong desire among healthy people, patients with chronic diseases, and healthcare providers for a self-assessment portal that can collect patient-reported outcome metrics and deliver personalized feedback.